2021
DOI: 10.1038/s41467-021-24614-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of water on colloidal quantum dot solar cells

Abstract: Almost all surfaces sensitive to the ambient environment are covered by water, whereas the impacts of water on surface-dominated colloidal quantum dot (CQD) semiconductor electronics have rarely been explored. Here, strongly hydrogen-bonded water on hydroxylated lead sulfide (PbS) CQD is identified. The water could pilot the thermally induced evolution of surface chemical environment, which significantly influences the nanostructures, carrier dynamics, and trap behaviors in CQD solar cells. The aggravation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 70 publications
0
37
0
Order By: Relevance
“…Zherebetskyy et al showed that dissociated water molecules can hydroxylate the PbS NC surface . More recently, Shi et al examined the detailed impact of surface hydroxylation on PbS NC fusion, electronic structure, and device performance . In all cases, it is important to perform the purification process in a short period of time to minimize exposure to air or preferably perform the purification process in an inert atmosphere if possible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Zherebetskyy et al showed that dissociated water molecules can hydroxylate the PbS NC surface . More recently, Shi et al examined the detailed impact of surface hydroxylation on PbS NC fusion, electronic structure, and device performance . In all cases, it is important to perform the purification process in a short period of time to minimize exposure to air or preferably perform the purification process in an inert atmosphere if possible.…”
Section: Methodsmentioning
confidence: 99%
“…86 More recently, Shi et al examined the detailed impact of surface hydroxylation on PbS NC fusion, electronic structure, and device performance. 87 In all cases, it is important to perform the purification process in a short period of time to minimize exposure to air or preferably perform the purification process in an inert atmosphere if possible. For the most reproducible results, ligand coverage can be determined qualitatively using FTIR 75,88 and quantitatively via 1 H-NMR; 51,85,89,90 typical ligand coverages are in the range of 1−5 ligands/nm 2 .…”
Section: Experimental Design Considerationsmentioning
confidence: 99%
“…7 Imbalanced size distribution would cause charge trapping at larger dots with lower band gap. 8 Similar problems could occur when nonpassivated surface defects of QDs function as trapping sites. 9,10 Correspondingly, enormous efforts were given to develop passivation skills as well as to improve the size uniformity.…”
Section: Introductionmentioning
confidence: 98%
“…Second, the charge transport within QD films is predominantly determined by the size uniformity of the QDs as well as their surface property . Imbalanced size distribution would cause charge trapping at larger dots with lower band gap . Similar problems could occur when nonpassivated surface defects of QDs function as trapping sites. , Correspondingly, enormous efforts were given to develop passivation skills as well as to improve the size uniformity. , Third, lack of back surface field in the QD layer may deteriorate carrier extraction from the backside.…”
Section: Introductionmentioning
confidence: 99%
“…In the former, the successful demonstration of solution-phase ligand exchange has enabled highly passivated CQDs. However, it has recently been found that oxidative species in ambient conditions, such as oxygen and humidity, result in oxidation of the CQD surface, causing detrimental effects on the device. In the latter case, chemical treatments have improved electronic coupling over the CQDs by connecting them, but this approach conversely compromises the surface passivation, such as merging of CQDs …”
mentioning
confidence: 99%